A Scientific Foundation of Simulation Games for the Analysis and Design of Complex Systems. (June 2018) - Lukosch, Heide K.; Bekebrede, Geertje; Kurapati, Shalini; Lukosch, Stephan G.
Background . The use of simulation games for complex systems analysis and design has been acknowledged about 50 years ago. However, articles do not combine all salient factors for successfulsimulation games, and often stem from a clear view of one particular field of science only. With combining multiple disciplines, connect analysis and design as well as research and practice, we provide deep insights in design and use ofsimulation games . Aim . This article analyzes the design and evaluation process of a variety of game-based projects and activities, using existing scientific concepts and approaches, in order to establishgames as a valid research tool . Our focus lies on the approach towards the use of games as design instrument; using them as an intervention in a larger, complex context, in order to design this context. With our contribution, we aim at providing insights and recommendations on the design and use ofgames as valid research tools, the limitations of this use, possible pitfalls, but also best practices. Method . We carried out a literature review of related work to identify the most important scientific concepts related to our approach of game design. Further use of combined quantitative and qualitative case study analyses highlights the design process and results of our owngame studies . Results . The analyses yielded a consolidated conceptualization of simulation games as research instruments in complex systems analysis and design. The results also include methods for the evaluation ofsimulation games, additional evaluation methods, and limitations to usesimulation games as research instruments. Conclusions . We propose guidelines for using simulation games as research instruments that may be of value to practitioners and scientists alike. Recommendation . We recommend practitioners and scientists to apply the guidelines presented here in their efforts to analyze and design complex systems.